Prossumidores nostálgicos: reflexões sobre a obsolescência das mídias audiovisuais - Marcelo Enrique Lopez da Cunha Pereira (2013)
The audiovisual succeeded throughout its history at giving tools to amateurs so they could experience the production of content, either to record ones life or in the making of movies. However, the very nature of film as mass media, and the proliferation and virtualization of formats and democratization of content production tools provided by the digital revolution masked even more the problems of the frailty of audiovisualsupport. It is understood by layers (or stages) the participation of the modern individual with the audiovisual medium: the collector, who keeps the productions so that they can come to future generations; and the prosumor, consumer and content producer, a new and asleep element of the conceptual point of view. This study follows the history of audiovisual media for domestic consumption and tries to understand the prosumor as an agent in the process of safeguarding the audiovisual memory.